Thin films of magnetically doped topological insulator with carrier-independent long-range ferromagnetic order - Chang, Cui-Zu (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.